Altered interferon defense in children with dynamically changed infectious mononucleosis - E. A. Kukushkina (Sankt-Peterburg : NIIÈM imeni Pastera, 2021)
The state of the interferon system in 38 children with acute infectious mononucleosis (IM) caused by the Epstein—Barr virus was analyzed. Interferon status was examined in accordance with F.I. Ershov method based on assessing related biological activity by measuring interferon level in the blood serum or produced by blood cells. The aim of the study was to gain scientifically justified data for use of interferon preparations or interferonogens in IM combination therapy. For this, interferon status in children with acute IM was compared with that one not only in control group (30 healthy children, aged 3—6 and 20 children, aged 7—14 years, examined earlier to create an intra-laboratory interferon normal range), but also in children with lacunar angina or acute respiratory viral infection, hospitalized in the same department of the clinic and comparable with the main group in severity of the condition. In addition, we assessed changes in IFN-status in IM patients receiving no interferon preparations, one month after the disease onset. The study showed that patients with moderate acute IM were featured with decreased potential of blood leukocytes to virus-induced IFNa and mitogen-induced IFNy production observed with almost similar or some lower rate as in the control group of children hospitalized with angina or acute respiratory viral infection. Peripheral blood cells from moderate acute IM patients in the 3-6-year age group were found to produce virtually unaltered interferon level, whereas almost sole IFN-alpha production was affected in 7-14-year-old patients. Moreover, in 7-14-year old patients the level 1 and level 2 of IFNa deficiency was observed in 38% and 6% of cases, respectively. It is likely it was just this patient group requiring administration of any IFNa replacement therapy. As few as 12 children were re-examined after discharge from the clinic. Initially, prevalence and severity level of impaired interferon production in this subgroup did not differ from that one for total patient sample, whereas 1 month later a host potential to produce both IFNa and IFNy even without therapy acting on interferon system was noted to be moderately augmented.